The first chromosome-level genome of the lappet moth Trabala vishnou (Lepidoptera: Lasiocampidae) - Ya-Lin Pu; Tian-Zhu Yan; Hao-Ran Wang; Kai Gao; Hai-Peng Zhao (Scientific Data)
Abstract Trabala vishnou (Lefèbvre, 1827) (Lepidoptera: Lasiocampidae) is a destructive leaf-eating pest that causes severe damage to forest ecosystems, leading to substantial economic losses. Herein, we sequenced and assembled a high-quality chromosome-level genome of T. vishnou using a combination of Illumina reads, PacBio HiFi reads, and High throughput Chromosome Conformation Capture (Hi-C) technologies. The genome size is 561.86 Mb and spans 25 chromosomes, exhibiting a high level of contiguity (scaffold/contig N50 = 21.75 Mb/20.67 Mb). Benchmarking Universal Single-Copy Orthologs (BUSCO) analysis a 99.5% completeness score for this genome assembly. Repeat elements constitute 62.66% of the genome. A total of 1,630 non-coding RNAs and 12,895 protein-coding genes have been identified within the genome. The first chromosome-level genome of T. vishnou serves as a valuable reference for elucidating the evolution of functional traits in Lasiocampidae family and will facilitate the development of strategies for controlling defoliating pests.